A survey of firewall technology based on image content filtering - DONG Kai-kun; HU Ming-zeng; FANG Bin-xing (Tongxin xuebao)
In this paper, status quo of firewall technology based on image content filtering is introduced. Typical firewall system architecture is given, and key techniques of the system are analyzed and discussed.